Divórcio e conflito interparental : indicadores emocionais e cognitivos dos/das filhos/as - Böer, Fernanda Monteiro (2018)
Parental divorce is a social phenomenon, growing and current, which leads to many changes in family life, especially in children lives. Several risk factors associated with marital disruption may adversely affect child development, including interparental conflict. In this sense, the present study had the objective of evaluating the emotional and cognitive indicators of children exposed to different levels of interparental conflict whose parents had, in prosecution, a judicial process of divorce. To do so, a comparative study was carried out, divided into three groups: low exposure to interparental conflict (G1), medium exposure to interparental conflict (G2) and high exposure to interparental conflict (G3). During the investigation, the following instruments were used: sociodemographic questionnaire, Children's Perceptions Scale on Interparental Conflict, Human Figure Drawing-III, the Pfister Colored Pyramids Test. The sample consisted of 27 children seven to 11 years old (M = 8.96 and SD = 1.40) and of both sexes (F = 16 and M = 11). Descriptive statistics of HFD-III and TPC variables were performed both in the total sample and in the results presented by the groups. For the comparison between the groups, inferential statistical analysis was performed through Kruskal Wallis Test and Fisher's Exact Test. Regarding cognitive performance, the participants showed a predominance of results considered inferior, which could be explained by other variables, such as family socioeconomic level and the type of school the child attends to. The groups revealed similar results regarding cognitive performance, suggesting that the variable interparental conflict did not influence the participants' cognitive outcome. Regarding the emotional indicators, the total sample presented results compatible with the normative sample of the test. However, in the comparison between the groups, it was observed that children who perceived higher levels of interparental conflict revealed excessive emotional control, tendency to repress feelings and situations with a lot of affective stimulation, rigid behavior, passivity, inhibition, feelings of inferiority and low productivity. Based on these findings, which corroborate with the results of previous research, it was concluded that interparental conflict, rather than divorce from parents, may cause harm to child development.